2020
DOI: 10.1038/s41598-020-66961-3
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic stabilization by nitrosoglutathione-induced thiol modifications in the stromal interaction molecule-2 luminal domain suppresses basal and store operated calcium entry

Abstract: Stromal interaction molecule−1 and −2 (STIM1/2) are endoplasmic reticulum (ER) membrane-inserted calcium (Ca 2+) sensing proteins that, together with Orai1-composed Ca 2+ channels on the plasma membrane (PM), regulate intracellular Ca 2+ levels. Recent evidence suggests that S-nitrosylation of the luminal STIM1 Cys residues inhibits store operated Ca 2+ entry (SOCE). However, the effects of thiol modifications on STIM2 during nitrosative stress and their role in regulating basal Ca 2+ levels remain unknown. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
0
2
0
2
Order By: Relevance
“…Like STIM1, STIM2 has cysteine residues in its luminal domain; two of them Cys53, and Cys60 are conserved with STIM1, and one Cys15 is unique to STIM2. All three residues can be S-nitrosylated leading to a synergistic stabilization of the EF-SAM region, reduced basal cytosolic Ca 2+ and lower STIM2-mediated SOCE ( Novello et al, 2020 ). In contrast to STIM1, STIM2 constitutively clusters at the ER-PM junctions in both mobile and immobile clusters with changes in both IP 3 R function and ER Ca 2+ levels being the driving factors contributing to the increases or decreases of immobile clusters of STIM2 in ER-PM junctions ( Ahmad et al, 2022 ).…”
Section: Stims—gene and Protein Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Like STIM1, STIM2 has cysteine residues in its luminal domain; two of them Cys53, and Cys60 are conserved with STIM1, and one Cys15 is unique to STIM2. All three residues can be S-nitrosylated leading to a synergistic stabilization of the EF-SAM region, reduced basal cytosolic Ca 2+ and lower STIM2-mediated SOCE ( Novello et al, 2020 ). In contrast to STIM1, STIM2 constitutively clusters at the ER-PM junctions in both mobile and immobile clusters with changes in both IP 3 R function and ER Ca 2+ levels being the driving factors contributing to the increases or decreases of immobile clusters of STIM2 in ER-PM junctions ( Ahmad et al, 2022 ).…”
Section: Stims—gene and Protein Structuresmentioning
confidence: 99%
“…They also showed that upon the induction of oxidative stress the oxidation of Cys313 on STIM2 is modified promoting a reduction in SOCE through the prevention of STIM2 oligomerization. It has also been shown that in response to the NO donor, nitrosoglutathione, STIM2 was S-nitrosylated at cysteines 15, 53, and 60 in HEK cells which was required for the stabilization of STIM2 ( Novello et al, 2020 ). Like STIM isoforms, Orai isoforms are also subject to redox regulation.…”
Section: Redox Regulation Of Stim and Orai Proteinsmentioning
confidence: 99%
“…Su extremo N-terminal se sitúa en el lumen del RE, donde se localiza el sitio de unión a Ca 2+ , llamado motivo-𝛼 Esteril EF (SAM). En cuanto a su extremo C-terminal, da a la cara citosólica y presenta tres segmentos hélices arrolladas o coiled-coil (CC1-3) seguidos de una región flexible (figura 2.15) (Hooper et al (2013), Fahrner et al (2017, Novello et al (2020), Grabmayr, Romanin, and Fahrner (2021), Tiffner et al (2021), Berlansky et al (2021)). A continuación, se desarrollan en más detalle las diferentes regiones y dominios de estas proteínas, comenzando desde el extremo N-terminal (figura 2.15).…”
Section: Rico En Kunclassified
“…A continuación, se desarrollan en más detalle las diferentes regiones y dominios de estas proteínas, comenzando desde el extremo N-terminal (figura 2.15). Además, se explicarán las diferencias entre las dos isoformas más convencionales, STIM1 y STIM2.2, y las implicaciones funcionales que estas tienen que, probablemente, prevengan la sobrecarga de Ca 2+ mediada por STIM2.2 (Hooper et al (2013), Fahrner et al (2017, Novello et al (2020), Grabmayr, Romanin, and Fahrner (2021), Tiffner et al (2021), Berlansky et al (2021)).…”
Section: Rico En Kunclassified